2018
DOI: 10.1016/j.ctim.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Reporting quality of music intervention research in healthcare: A systematic review

Abstract: Problems with reporting quality impedes meaningful interpretation and cross-study comparisons. Inconsistent and misapplied terminology also create barriers to interprofessional communication and translation of findings to patient care. Improved reporting quality and creation of shared language will advance scientific rigor and clinical relevance of music intervention research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 198 publications
0
78
0
5
Order By: Relevance
“…However, the clinical relevance of the observed results are under debate and additional studies are needed to further investigate this. In this regard a systematic review on the quality of available www.nature.com/scientificreports/ music intervention studies discusses the importance of high quality studies which give sufficient information regarding the music intervention applied in order to improve the clinical relevance of music interventions 35 . Additionally, our study revealed that STAI-Trait scores, measuring anxiety as a personality trait, positively correlated with preoperative subjective anxiety scores.…”
Section: Main Findingsmentioning
confidence: 99%
“…However, the clinical relevance of the observed results are under debate and additional studies are needed to further investigate this. In this regard a systematic review on the quality of available www.nature.com/scientificreports/ music intervention studies discusses the importance of high quality studies which give sufficient information regarding the music intervention applied in order to improve the clinical relevance of music interventions 35 . Additionally, our study revealed that STAI-Trait scores, measuring anxiety as a personality trait, positively correlated with preoperative subjective anxiety scores.…”
Section: Main Findingsmentioning
confidence: 99%
“…2018 Associação Brasileira de Cognição e Artes Musicais -ABCM Um grande desafio dos estudos de intervenção é estabelecer critérios objetivos para a definição de uma intervenção musical. Robb et al, (2018) sugerem que seja levada em consideração uma descrição detalhada das estratégias empregadas na intervenção, garantindo fidedignidade nos relatos dos experimentos. Além disso, propõem que a melhoria da qualidade dos relatórios e a criação de linguagem compartilhada promoverão o rigor científico e a relevância clínica da pesquisa sobre intervenção musical.…”
Section: Discussionunclassified
“…The second study, by Robb et al (2018), has less scope but provides much more detail. It examines reporting quality of music interventions in healthcare by comparing the latest literature (187 papers from 2010 to 2015) against a set of guidelines specific to the field (Robb, Burns, & Carpenter 2011).…”
Section: Two Worrying Patterns Of Behavior In Experimental Psychologymentioning
confidence: 99%
“…These attitudes, though related to communication, need not impact research reproducibility, however. Therefore, in section 5, I bring up some direct evidence for my central claim -I discuss four empirical studies: (a) by Grant et al (2013), who investigate quality of reporting in psychological and social intervention trials in clinical psychology, criminology, education and social work, (b) by Robb et al (2018), who examine compliance with field specific reporting guidelines in the latest studies of music-based interventions in healthcare, (c) by Brown et al (2014), who investigate descriptive completeness of psychological papers published in 2010, and (d) by Carp (2012), who focuses on reports of fMRI studies. They all indicate that quality of reporting relevant to reproducibility is poor: roughly over 50% of the reports are seriously deficient in this respect and even about 80-90% of the studies may be irreproducible due to incomplete reporting.…”
Section: Introductionmentioning
confidence: 99%